INTEGRATING AI –DRIVEN ECONOMIC FORECASTING IN CORPORATE FINANCIAL DECISIONS: A DECISION THEORY PERSPECTIVE - Christina Effina Putri dwi; Agus Wibowo (Jurnal Akuntansi dan Bisnis, 2026)
Global economic uncertainty has pushed companies to make financial decisions that are faster, more accurate, and adaptable. However, the use of Artificial Intelligence (AI) to predict economic conditions in real-time and support corporate financial decisions is still limited-especially in developing countries. This study aims to design an AI-based model capable of forecasting global economic fluctuations and analyzing its impact on corporate financial strategy. A qualitative approach was applied, using case studies and descriptive-exploratory analysis based on secondary data and relevant AI system documentation. The results show that the AI model can identify key economic indicators and provide predictions that enhance financial planning accuracy. Moreover, the model strengthens decision-making by combining data-driven strategies with managerial intuition. This research contributes both theoretically and practically to the use of AI in supporting financial decision-making, particularly in volatile economic environments.